Research on The Development and Integration of Chinese Ancient Architecture in Modern Urban Planning - Cao, Xuwei (Transactions on Engineering and Technology Research, 2024)
This paper studies and analyzes the development cases of ancient buildings in different historical backgrounds. It mainly compares the Beijing City Wall which was destroyed with The Dujiangyan Water Conservancy Project and Beijing-Hangzhou Grand, which are protected and sustainably developed in modern society Canal reflects the development and integration of ancient Chinese architecture in urban planning. The study explores how to promote sustainable development policies while preserving and utilizing ancient buildings, through the combination of modern technology and traditional architecture, to achieve the inheritance and innovation of cultural heritage in the city. The study pointed out that through reasonable protection and renovation, ancient buildings can not only preserve the historical culture of the city but also bring economic and social benefits to the city through innovative design. Several cases of positive and negative impacts are mentioned in the paper, which is a valuable experience and lesson for other relics and ancient buildings. In addition, the paper further points out the future difficulties in the development and integration of Chinese ancient architecture in urban planning and will continue to explore how to realize the transformation of modern functions of historical buildings based on cultural inheritance, to actively shape the future development direction of the city.